Relationship between crop load, N, P, K, Ca, Mg and starch content and the dieback of catimor (Coffea arabica L.) - de Carvalho, Carlos Henrique Siqueira; Rena, Alemar Braga; Pereira, Antônio Alves; Cordeiro, Antônio Teixeira (Pesquisa Agropecuaria Brasileira, 1993)
Dieback of the progeny of Coffea arabica L. Catimor UFV-1359 was studied by altering the crop level through thinning of flowers and fruits, and determining the leaf contents of N, P, K, Ca and Mg and starch content in the leaves and plagiotropic branches. Dieback was closely related to the amount of crop on the tree and was not observed in trees whose flowers were removed. No relationship was found between the dieback of the progeny Catimor UFV-1359 and the leaf content of N, P, K, Ca and Mg. The starch content of both leaves and branches was not always related to the dieback incidence and therefore might not be considered as a good criterion to evaluate coffee tree vigor.